2006
DOI: 10.1002/bdra.20233
|View full text |Cite
|
Sign up to set email alerts
|

Mouse embryonic stem cells are not susceptible to cytomegalovirus but acquire susceptibility during differentiation

Abstract: BACKGROUND:Cytomegalovirus (CMV) is the most significant infectious cause of congenital anomalies of the central nervous system caused by intrauterine infection in humans. The timing of infection and the susceptibility of cells in early gestational stages are not well understood. In this study we investigated the susceptibility of embryonic stem (ES) cells to CMV infection during differentiation. METHODS: ES cell lines were established from transgenic mice integrated with the murine CMV (MCMV) immediate-early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 49 publications
(59 reference statements)
4
33
0
Order By: Relevance
“…At late gestation (E15.5), the brain is a preferential site of infection, and obvious brain damage (porencephaly) and productive infection are observed when MCMV is injected into the cerebral ventricles (30). In vitro, murine embryoderived pluripotent stem cells (ePSCs) are nonpermissive to MCMV infection (31,32); however, they gain susceptibility and become permissive during differentiation (32). These results support the hypothesis that the stage of gestation and the differentiation status of progenitor/stem cells contribute to the susceptibility to CMV infection and clinical outcome.…”
mentioning
confidence: 99%
“…At late gestation (E15.5), the brain is a preferential site of infection, and obvious brain damage (porencephaly) and productive infection are observed when MCMV is injected into the cerebral ventricles (30). In vitro, murine embryoderived pluripotent stem cells (ePSCs) are nonpermissive to MCMV infection (31,32); however, they gain susceptibility and become permissive during differentiation (32). These results support the hypothesis that the stage of gestation and the differentiation status of progenitor/stem cells contribute to the susceptibility to CMV infection and clinical outcome.…”
mentioning
confidence: 99%
“…It was shown that the concentration of heparan sulfate in the cell surface, the presence of β1-integrin and vimentin, and the nuclear pore density is important for the attachment, penetration, and internalization to the nucleus (Kawasaki et al 2011). In mouse models, it has been observed that embryonic stem cells cannot be infected with CMV and they acquire susceptibility through differentiation (Matsukage et al 2006;Kawasaki et al 2011). However, differentiated neurons are also refractory to the infection and this may suggest that only during a precise period during differentiation, the cells can be infected (Cheeran et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the virus to infect the developing fetal brain is a key factor in its neuropathogenesis (3)(4)(5)(6)(7)(8). While considerable experimental data were obtained from newborn and embryonic mouse models (6,(9)(10)(11)(12)(13)(14)(15), the strict species specificity precludes animal models of HCMV. Recent studies in human neuronal progenitor cells (NPC) derived from fetal and neonatal brains have revealed productive HCMV infection of NPC, with resultant functional alterations (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%